Hamburg Pluvial Flood Risk Map - Malte von Szombathely; Jörn Behrens; Franziska S. Hanf; Marc Lennartz; Benjamin Poschlod; Anastasia Vogelbacher; Jana Sillmann (2025)
The "Hamburg Pluvial Flood Risk Map" aims to improve our understanding of the drivers, dynamics and interactions of climate-induced (disaster) risks in Hamburg. Following the risk framework of the IPCC, we calculate a risk index based on hazard, exposure and (social) vulnerability. In this sense, we combine data from the previously published Social Vulnerability Index (von Szombathely et al., 2023) with novel meter-scale hydraulic simulations of urban flooding provided by the heavy rain hazard map of the city of Hamburg (BKG/FHH 2023). We have enhanced the modeling of social vulnerability by applying the TOPSIS method and the Shannon Entropy procedure. and propose a high-resolution exposure modeling designed for urban flooding, with different exposure layers threatening health and restricting mobility and accessibility. We show that fundamentally new spatial patterns emerge for pluvial flood risk in Hamburg, which differ from familiar socio-economic urban structures and at the same time differ clearly from a pure representation of the hazard. Presented through high-resolution spatial maps, this analysis aids in identifying adaptation needs and prioritizing policy measures for climate change adaptation.References:BKG/FHH 2023. Eine Starkregen-Gefahrenkarte für Deutschland. https://www.business-geomatics.com/2023/02/02/eine-starkregen-gefahrenkarte-fuer-deutschland/von Szombathely M., Hanf F. S., Janka B., Meier L., Ossenbrügge J., Pohl T. 2023. An Index-Based Approach to Assess Social Vulnerability for Hamburg, Germany: International journal of disaster risk science. 14, 5, p. 782-794 13 p. DOI: 10.1007/s13753-023-00517-7